Incidence and risk factors of suicide reattempts within 1 year after psychiatric hospital discharge in mood disorder patients - Chidchanok Ruengorn (2018)
Background: The incidence and risk factors of suicide reattempts within 1 year after psychiatric hospital discharge in mood disorder patients remain uninvestigated in Thailand. Objective: To determine incidence and risk factors of suicide reattempts within 1 year after psychiatric hospital discharge in mood disorder patients. Methods: A retrospective cohort study was conducted by reviewing medical charts at Suanprung Psychiatric Hospital, Chiang Mai, Thailand. Mood disorder patients, diagnosed with the International Statistical Classification of Diseases and Related Health Problems 10th Revision codes F31.x, F32.x, and F33.x, who were admitted owing to suicide attempts between October 2006 and May 2009 were eligible. The influence of sociodemographic and clinical risk factors on suicide reattempts was investigated using Cox's proportional-hazards regression analysis. Results: Of 235 eligible mood disorder patients, 36 (15.3%) reattempted suicide (median 109.5 days, range 1-322), seven (3.0%) completed suicide (median 90 days, range 5-185), and 192 (84.2%) neither reattempted nor completed suicide during follow-up. Of all nonfatal suicide reattempts, 14 patients (38.9%) did so within 90 days. Among suicide completers, one (14.3%) did so 5 days after discharge, and four (57.1%) did so within 90 days. The following three risk factors explained 73.3% of the probability of suicide reattempts: over two previous suicide attempts before the index admission (adjusted hazard ratio [HR] 2.48; 95% confidence interval [CI] 1.07-5.76), being concomitantly prescribed typical and atypical antipsychotics (adjusted HR 4.79; 95% CI 1.39-16.52) and antidepressants, and taking a selective serotonin reuptake inhibitor alone (adjusted HR 5.08; 95% CI 1.14-22.75) or concomitantly with norepinephrine and/or serotonin reuptake inhibitors (adjusted HR 6.18; 95% CI 1.13-33.65). Conclusion: Approximately 40% of suicide reattempts in mood disorder patients occurred within 90 days after psychiatric hospital discharge. For mood disorders and when there have been over two previous suicide attempts, prescribed antipsychotics or antidepressants may help predict suicide reattempts. © 2011 Ruengorn et al, publisher and licensee Dove Medical Press Ltd.